2016
DOI: 10.1007/s00484-016-1202-3
|View full text |Cite
|
Sign up to set email alerts
|

The major influence of the atmosphere on intracranial pressure: an observational study

Abstract: The impact of the atmosphere on human physiology has been studied widely within the last years. In practice, intracranial pressure is a pressure difference between intracranial compartments and the surrounding atmosphere. This means that gauge intracranial pressure uses atmospheric pressure as its zero point, and therefore, this method of pressure measurement excludes the effects of barometric pressure's fluctuation. The comparison of these two physical quantities can only take place through their absolute val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Imbalance of atmospheric pressure and ICP, disruption of CSF flow dynamics, and disruption of CBF and metabolism have been postulated to cause SoT 6–11,18,33. Under normal physiological conditions atmospheric pressure correlates with intracranial pressure with barometric changes usually insufficient to affect intracranial physiology significantly due to the protective effect of the calvarium 34. Epidural pressure monitoring of postcraniectomy patients with large skull defects undergoing cranioplasty demonstrates initially elevated ICPs preoperatively in a subset of patient with reversable neurological deficits 10.…”
Section: Discussionmentioning
confidence: 99%
“…Imbalance of atmospheric pressure and ICP, disruption of CSF flow dynamics, and disruption of CBF and metabolism have been postulated to cause SoT 6–11,18,33. Under normal physiological conditions atmospheric pressure correlates with intracranial pressure with barometric changes usually insufficient to affect intracranial physiology significantly due to the protective effect of the calvarium 34. Epidural pressure monitoring of postcraniectomy patients with large skull defects undergoing cranioplasty demonstrates initially elevated ICPs preoperatively in a subset of patient with reversable neurological deficits 10.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant number of published papers showing some kind of association between atmospheric pressure change and SAH incidence, probably because papers with negative results are rarely published, as pointed previously 31 . Furthermore, several authors speculate that atmospheric pressure may affect blood or intracranial pressure, leading to possible IA rupture 40,42 . Still, at this time, there is no satisfactory explanation for the association between atmospheric pressure changes and SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that climate or the Moon may influence humans and animals and the occurrence of various diseases [8][9][10]. A prospective study suggested that atmospheric pressure positively impacts absolute intracranial pressure in humans [11]. More specifically, some authors suggested a role of climate conditions in intracerebral hemorrhage and SAH [12][13][14][15][16][17][18], but reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%